2007
DOI: 10.1016/j.saa.2006.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy of racemic and enantiomeric forms of atenolol

Abstract: The molecular structure of conformational isomorphs given by X-ray diffraction for racemic and enantiomeric atenolol were optimized at the HF/6-31G* level of theory and the infrared spectra of the structure were calculated. These spectra are used to characterize the differences between the various atenolol conformers.The spectra of the (R,S)-and S-atenolol solid forms were recorded and the bands corresponding to the functional groups identified with the aid of the calculated spectra, fitting analysis, temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…In the infrared spectrum of ATE ( Figure 3 a), the bands were identified as follows: 3342 cm −1 for symmetric and asymmetric stretching N-H, 2961 cm −1 for alcoholic OH, 1631 cm −1 for C=O amide, and 1235 cm −1 for alkyl aryl ether. The aforementioned observations match with the FTIR spectra relating to ATE as documented in reference [ 21 ]. A number of changes in the FTIR spectra were observed after the formation of the ATE-β-CD inclusion complex.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In the infrared spectrum of ATE ( Figure 3 a), the bands were identified as follows: 3342 cm −1 for symmetric and asymmetric stretching N-H, 2961 cm −1 for alcoholic OH, 1631 cm −1 for C=O amide, and 1235 cm −1 for alkyl aryl ether. The aforementioned observations match with the FTIR spectra relating to ATE as documented in reference [ 21 ]. A number of changes in the FTIR spectra were observed after the formation of the ATE-β-CD inclusion complex.…”
Section: Resultssupporting
confidence: 86%
“…Therefore, with the purpose of increasing the solubility, ATE and PRO were complexed with β-CD and with 2-hydroxypropyl-β-CD to form inclusion complexes [ 17 , 18 ]. A literature survey reveals that some methods have been used to determine ATE and PRO individually in pharmaceutical formulations and biological fluids like capillary electrophoresis [ 19 , 20 ], spectrophotometric methods [ 21 , 22 ], high-performance liquid chromatography [ 15 , 23 ], spectrofluorometric methods [ 24 , 25 ], and gas chromatography [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the AT 0.6% powder, the bands ascribed to stretching and in-plane deformation of the N\H group were at 3160 cm −1 and 1637 cm −1 , respectively in agreement with previous reports [68]. According to Soares et al [63], the C_O stretching band of the AA is expected to be found around 1730 cm − 1 .…”
Section: Ft-ir Characterizationsupporting
confidence: 89%
“…3. This sample maintained the crystalline structure (the reflections were in the same angular positions than the ones of AT op ), however the crystallinity degree [80] and crystal habit were different as consequence of the process that it was subjected to [68].…”
Section: Crystallographic Characterizationmentioning
confidence: 98%
“…The formation of interactions between the At and the MIL-100(Ti) is evidenced by Fourier transform infrared spectroscopy (FTIR) by comparing the spectra of free At to that of the empty and the At loaded material (At@MIL-100(Ti)). Specifically, there is a shift in the wavelengths of pure At (from 2964 and 2922 cm −1 to 2955 and 2925 cm −1 for At and At@MIL-100(Ti), respectively; see SI, Figure S5), characteristic of the ν(C-H) group of the C9 (near the ether group C9-O-benzene) 40 . In contrast, the MIL-125-NH 2 was able to adsorb up to 66.6 ± 1.1% of At and 50.2 ± 3.4% of SMT after 5 h. However, the release of the previously adsorbed EOCs was evidenced after 1 h, probably related with the degradation of the framework during the drug adsorption process (SI, Figure S2&S3).…”
Section: Screening Of the Smt And At Photodegradation And Mof Stabili...mentioning
confidence: 98%